(untitled) (Itinera, 2012)
Starting from Arthur Danto’s The Philosophical Disenfranchisement of Art, we take into consideration two works of art – Marcel Duchamp’s Fountain and Andy Warhol’s Brillo Box – where the notion of interpretation, according to the American philosopher, plays a prominent role in the process of creation. By focusing on the legacy of Duchamp’s and Warhol’s works, in the light of the Deleuzian notions of Humor and Irony, this paper shows that the two artists can be considered as the first promoters of the “aesthetics of surfaces”. Particularly, Warhol seems to listen to the “superficial claim” of the artificial, that is to say a copy of a copy, that can be brought «to the point where is reversed into the simulacrum».